2014
DOI: 10.4049/jimmunol.1303370
|View full text |Cite
|
Sign up to set email alerts
|

ADAM9 Is a Novel Product of Polymorphonuclear Neutrophils: Regulation of Expression and Contributions to Extracellular Matrix Protein Degradation during Acute Lung Injury

Abstract: A disintegrin and a metalloproteinase domain 9 (ADAM9**) is known to be expressed by monocytes and macrophages. Herein, we report that ADAM9 is also a product of human and murine polymorphonuclear neutrophils (PMNs). ADAM9 is not synthesized de novo by circulating PMNs. Rather, ADAM9 protein is stored in the gelatinase and specific granules and the secretory vesicles of human PMNs. Unstimulated PMNs express minimal quantities of surface ADAM9, but activation of PMNs with degranulating agonists rapidly (within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 67 publications
(112 reference statements)
1
57
1
2
Order By: Relevance
“…In particular for ADAM9, it was demonstrated that it is able to cleave laminin and promote tumor cell invasion [27]. ADAM9 also efficiently degraded several other extracellular matrix (ECM) proteins besides laminin, including fibronectin, entactin and insoluble elastin, in a model of acute lung injury [28]. In our experimental model, silencing of ADAM9 significantly decreased ADAM15 expression, and it is known that one of the variants of ADAM15 is related to greater catalytic activity, resulting in more aggressive breast tumors [29].…”
Section: Discussionmentioning
confidence: 98%
“…In particular for ADAM9, it was demonstrated that it is able to cleave laminin and promote tumor cell invasion [27]. ADAM9 also efficiently degraded several other extracellular matrix (ECM) proteins besides laminin, including fibronectin, entactin and insoluble elastin, in a model of acute lung injury [28]. In our experimental model, silencing of ADAM9 significantly decreased ADAM15 expression, and it is known that one of the variants of ADAM15 is related to greater catalytic activity, resulting in more aggressive breast tumors [29].…”
Section: Discussionmentioning
confidence: 98%
“…These glycoproteins transduce both biochemical and mechanical signals between ECM and cells to influence cell survival, differentiation, and migration (89). Laminins are degraded by serine protease and metalloprotease family members (90,91). Laminin 332 (also known as laminin 5) is a component of multiple basement membranes and is implicated in hemidesmosome formation (92).…”
Section: Laminin-derived Matrikinesmentioning
confidence: 99%
“…ADAM9 knockout mice (129Sv ϫ CD57BL/6) do not show an obvious phenotype other than reduced neovascularization in the cornea pocket assay (204). In the lung, ADAM9 deficiency (C57BL/6) conferred protection against LPS-or bleomycin-induced lung inflammation (159). This protection was explained by the ability of ADAM9 to degrade lung elastin fibers leading to reduced lung compliance and disruption of the alveolar-capillary barrier.…”
Section: Other Adamsmentioning
confidence: 96%
“…ADAM9 is expressed at a low level in the lung and is upregulated in experimentally induced acute lung inflammation, a finding that was explained by an increase in leukocyte-derived ADAM9 (159). In vitro, the protease was found on monocytic cells, neutrophils, epithelial cells, and vascular SMCs.…”
Section: Other Adamsmentioning
confidence: 96%
See 1 more Smart Citation